Hard water treatment with synthesized carbon nanoparticles of Phyllanthus emblica - Latha Vatchalan (Journal of Water and Environmental Nanotechnology, 2022)
Water is, indisputably, the most vital component of life on earth. Water is a life elixir and its hardness is defined by the high concentration of magnesium, calcium, lead, chromium, iron, and mercury. The hardness of water limits its domestic and industrial usage severely. Therefore it is essential to suggest a simple, low-cost, and robust method for hard water treatment by evaluating the results in terms of Physicochemical parameters.  In this paper, an efficient approach for hard water treatment by using synthesized carbon nanoparticles (C NPs) of Phyllanthus Emblica wood barks. The water samples are collected from the towns and villages located in Virudhunagar and Tuticorin District. For hardness treatment, in this work the physicochemical parameters considered are pH, TDS, dissolved Oxygen, Ca, Mg, Chloride, Alkalinity, and hardness levels. The experimental analysis, cleared that the proposed carbon nanoparticles synthesized from Phyllanthus Emblica wood barks are a very efficient and cost-effective solution.